Funding and its impact on the administration and organisational efficiency of technical vocational education and training institutions - Abede Jawara Mack (Springer, 2024)
Abstract In the present study, the author examines how the lack of funding can impact the administration and the organisational efficiency of technical vocational education and training (TVET) institutions (I). The research examines human capital development and TVET as instruments for propelling growth and development and contributing to Trinidad and Tobago's (T&T) economic and social advancements. The study explored how TVETIs can be a central pillar in the progress of T&T's development. The research material consists of 10 interviews with educational experts from four postsecondary TVETIs in T&T and the chief executive of T&T TVET's regulatory body. Focus groups and individual interviews were conducted with the leading regulator, instructors, managers, and a curriculum expert. The author utilised thematic analysis in the research by adopting a deductive approach. The data revealed several challenges that engulf the administration and management of TVETI in T&T, mainly because of financial woes. Three themes emerged from the data: Funding for Administration, Funding for Human Capital Development and Funding for Organisational Efficiency. Insightful revelations were unearthed from the educational experts, which were generated from the data which provide an in-depth perspective on the administration and management of TVET in T&T. The results show that T&T's education experts see funding as a significant challenge. Many argue that a lack of funding severely impacts their institutions, which erodes human capital development growth. The study concludes that a lack of funding can severely and has impacted TVET in several ways. An absence or a lack of funding brought the closure of top-notch schools used in the training and growth of teachers for the educational system. Human capital development and TVET were also highlighted as essential tools for economic and social deprivation. However, a better approach is needed to finance TVET moving forward.